On the performance of the Jackknifed Liu-type estimator in linear regression model - YILDIZ, NİLGÜN (TAYLOR & FRANCIS INC, 2018)
In this paper, we are proposing a modified jackknife Liu-type estimator (MJLTE) that was created by combining the ideas underlying both the Liu-type estimator (LTE) and the jackknifed Liu-type estimator (JLTE). We will also present the necessary and sufficient conditions for superiority of the MJLTE over the LTE and JLTE, in terms of mean square error matrix criterion. Finally, a real data example and a Monte Carlo simulation are also given to illustrate theoretical results.
Keywords: Liu-type estimators; Jackknifed estimator; Jackknifed Liu-type estimator; Mean squared error matrix; RIDGE-REGRESSION; BIAS